The role of socio-economic status in the relationship between pay, job and life satisfaction among South African graduates - Mfeketho, Yolanda (Organisational Psychology, 2022)
The employment of graduates globally has emerged as a critical issue of practical and theoretical interest for policymakers, government, academics, and practitioners. Faced with high rates of unemployment, first-time graduates often find themselves in jobs that are underpaying and unsatisfying which might ultimately affect their overall life satisfaction. This research presents the role of socioeconomic status in the relationship between pay and both job and life satisfaction among South African graduates from diverse socioeconomic groups. The purpose of the study is to explore and understand the relationship that exists between these variables and examine the role socioeconomic status plays in this interaction. The aim was to consider socioeconomic status as a moderator in the relationship between pay, job satisfaction, and life satisfaction as previous research has shown that socioeconomic status plays a significant role in determining graduate employment outcomes and prospects. A cross-sectional, descriptive design was employed, with data collected from 202 individuals who had graduated from tertiary education in South Africa and who were in employment at the time of data collection. The data indicates a positive relationship between pay received and job satisfaction among South African graduates. Similarly, a positive correlation was found between pay and life satisfaction. Furthermore, the relationship between pay and life satisfaction was found to be moderated by job satisfaction. The results of the study also indicated a spillover effect between job and life satisfaction, suggesting that job satisfaction and life satisfaction are positively correlated. The socioeconomic status of graduates in South Africa was found to play a role in the relationship between pay and job satisfaction. Furthermore, it was found that the difference between pay, and life satisfaction did not differ according to the socioeconomic status of the graduate. Based on these results scholars are advised to conduct further research to gain a deeper understanding of the underlying reasons for the racial group differences pertaining to job satisfaction.